2010
DOI: 10.1088/0031-9155/56/1/001
|View full text |Cite
|
Sign up to set email alerts
|

Detection of clustered microcalcifications using spatial point process modeling

Abstract: In this work we propose a spatial point process (SPP) approach to improve the detection accuracy of clustered microcalcifications (MCs) in mammogram images. The conventional approach to MC detection has been to first detect the individual MCs in an image independently, which are subsequently grouped into clusters. Our proposed approach aims to exploit the spatial distribution among the different MCs in a mammogram image (i.e., MCs tend to appear in small clusters) directly during the detection process. We mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 31 publications
4
33
0
1
Order By: Relevance
“…As a result, an unfocused transmit sequence was used on a Verasonics system (Verasonics, Redmond, WA) in order to acquire ultrasound RF frames at 2000 fps using a 2.5-MHz ATL P4-2 phased array. Such a high frame rate can be achieved by emitting unfocused circular ultrasound waves using a virtual focus located 10.2 mm behind the array (Figure 1-1) [15]. This allowed us to reach a high framerate while being able to get a full view of the heart for each transmit for the purpose of EWI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, an unfocused transmit sequence was used on a Verasonics system (Verasonics, Redmond, WA) in order to acquire ultrasound RF frames at 2000 fps using a 2.5-MHz ATL P4-2 phased array. Such a high frame rate can be achieved by emitting unfocused circular ultrasound waves using a virtual focus located 10.2 mm behind the array (Figure 1-1) [15]. This allowed us to reach a high framerate while being able to get a full view of the heart for each transmit for the purpose of EWI.…”
Section: Methodsmentioning
confidence: 99%
“…Using incremental strain estimation in the axial direction, EWI tracks the electromechanical wave (EW) which refers to the spatial propagation of the electromechanical activation through the heart. Previous studies have shown that the EW propagation is highly correlated with the underlying electrical activation sequence in all four chambers of the heart in normal canine hearts during sinus rhythm and various pacing protocols in silico and in vivo [15,2123]. EWI has also been shown capable of localizing regions of ischemia in a large animal model during intermediate levels of occlusion of the left anterior descending artery (LAD) [13], but not yet for detection and monitoring of MI.…”
Section: Introductionmentioning
confidence: 99%
“…40 To speed up the FROC analysis, in the experiments, we first applied a prescouting step as in Ref. 11, during which only the most suspicious regions in a mammogram image were identified for further consideration. This was based on the fact that the spatial extent of clustered MCs is typically limited (<1 cm 2 in area), while a whole mammogram image can be rather large in size.…”
Section: D4 Performance Evaluation Using Free-response Receiver Omentioning
confidence: 99%
“…5,6 In contrast, stochastic modeling methods are designed to exploit the statistical difference between MCs and their surroundings, which include, for example, higher-order statistics, 7 Markov random field, 8,9 Gaussian mixture models, 10 and spatial point process models. 11 Different from these approaches, machine learning methods treat the MC detection as a twoclass classification problem, wherein a decision function is determined with supervised learning from data examples in mammogram images. [12][13][14][15][16][17] Such methods include, for example, neural network, 12,13 boosted learning, 14 relevant vector machine (RVM), 15 and support vector machine (SVM).…”
Section: Introductionmentioning
confidence: 99%
“…Jing et al [4] investigated the spatial distribution of MC clusters in mammograms. They modeled MCs and background noise by gamma and Gaussian distribution, respectively.…”
Section: Introductionmentioning
confidence: 99%